STUDENTS’ PROBLEM IN SPEAKING ENGLISH AT SECOND GRADE OF SMA NEGERI 1 SIOMPU BARAT - La Mido (English Education Journal, 2019)
Students’ Problem in Speaking English at Second Grade of SMA Negeri 1 Siompu Barat, La Mido, FKIP Unidayan Baubau. This research aims to investigate the problems of speaking English at the second grade of SMA Negeri 1 Siompu Barat. This research applied a qualitative research, categorized as a case study. Two kinds of instruments of collecting data were used; observation and interview. In analyzing the data, the researcher used three steps inner activities analysis; data reduction, data presentation, and conclusion drawing. The result of the research showed that there are two problems of speaking English at the second grade of SMA Negeri 1 Siompu Barat, consist of psychological and language problems. The psychological problems were fear of mistake, shyness, anxiety, lack of confidence, and motivation. Meanwhile, the students’ speaking problem from language use were inhibition, nothing to say, low or even participation and mother tongue use. It can be concluded that there were some problems of speaking English at the second grade of SMA Negeri 1 Siompu Barat.